Atipical immunophenotype in a littoral cell angioma - Čolović Radoje; Suvajdžić Nada; Grubor Nikica; Čolović Nataša; Terzić Tatjana (Vojnosanitetski Pregled)
Background. Littoral-cell angioma (LCA) is a recently described benign vascular tumor of the spleen, whose imaging and pathologic characteristics have been discussed only by a few authors. The tumor is characterized by a mixture of papillary and cystic areas lined by neoplastic cells deriving from normal splenic lining - littoral cells. The neoplastic LCA cells express both endothelial and histiocytic antigens associated with CD8 negativity, compared with the normal endothelium of the venous sinuses of the spleen red pulp that only expresses endothelial antigens and CD8 positivity. Therefore, the typical and characteristic immunohistochemical pattern of the LCA is as follows: CD31, CD68, CD163, CD21, FVIII antigen positive; CD34, CD8 negative. Case report. We reported a 60-year-old male with moderate nodular splenomegaly with one large hypoechogenic solid lesion and mild thrombocytopenia in whom the diagnosis of LCA was made after the elective splenectomy. Namely, histopathological and immunohistochemical data allowed a final diagnosis of classical LCA in spite of CD21 negativity. As far as we know this is the first reported CD21-negative LCA patient. Histological specimens were presented and differential diagnoses discussed. Conclusion. Littoral-cell angioma is a very rare benign splenic neoplasm that should be considered in the differential diagnosis of multinodular splenomegaly, particularly if the patient has the signs of hypersplenism.